Bumdesa Crisis Communication: A Case Study Of The Animal Feed Business During The Covid-19 Pandemic Crisis In Karang Anyer Village In Indonesia - Faustyana Faustyana (International Journal Reglement & Society (IJRS), 2022)
This research examines crisis communication strategies during the COVID-19 pandemic because understanding the communication process is very important for BUMDesa to manage Animal Feed Businesses before, during, and after a crisis. The problem detected during the research was that animal feed managers need to understand the working principles of crisis communication in the marketing field during the Covid-19 pandemic crisis. The effect of the promotion of animal feed resulted in: Sales progress, hampered management being hampered, the number increase of animal feed piled up and rotting product demand decreasing, and consumers’ dissatisfaction with product quality. Constructivism paradigm is used with a qualitative method with a type of case study and purposive sampling is used to ensure quality and reliability. The result is useful in the field of communication science because it integrates qualitative methodologies for crisis communication through public relations in culinary tourism during the Covid-19 pandemic. BUMDesa actors as tourism public relations plan a strategy or business model in promoting products through understanding crisis communication for solutions to problems faced by animal feed and looking for loyal new market segments so that they have a positive effect on product promotion. The communication crisis was identified in the strategic planning and implementation by the manager, the director of BUMDesa, and the head of Karang Anyer Village. Then the promotion is through a crisis communication strategy, namely before, during, and post-crisis. Training on understanding effective crisis communication can help institutions to implement rapid responses, thus impacting the effective promotion and reputation of institutions.